Sekwencyjność a wielopoziomowe zarządzanie gospodarką ze szczególnym uwzględnieniem państw rozwijających się - Żukrowska, Katarzyna (Kwartalnik Kolegium Ekonomiczno-Społecznego. Studia i Prace, 2014)
The article shows possibilities of economic processes management in each economy, dividing them into internal methods and external methods. The later embrace conditions created by international environment as well as international organizations and relations established with them. Such management is strongly dependent on diversification of development of particular groups of economies, it takes into account national interests of different groups of economies and national, regional and global interests and differences among them. The concept is also strongly linked to stage of development of external institutional ties of each state. A separate part of the study is devoted to transmission channels which play an important role in helping to introduce certain solutions practiced and tested in other democracies. The subject covered in the article illustrates that only a limited number of countries make full use of the possibilities which were created by conditions of differentiated development and multilevel management, which creates an important component of the compound system, supporting it strongly. The conclusion of the article draws attention to the need of knowledge acquisition concerning sequencing of development and multilevel management of economic processes in each economy.